Pengaruh Latihan Push Up Terhadap Kemampuan Tolak Peluru Di Kelas Xi-2 Sma Negeri 7 Kediri - Petra Ardiansyah; Budiman Agung Pratama; Miftahkodin Miftahkodin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the effect of push-up training on improving shot put performance among 11th-grade students at SMAN 7 Kediri. Shot put is an athletic sport that requires a combination of arm muscle strength, proper technique, and explosive power to achieve optimal results. Push-up training was chosen as it is a simple yet effective method for enhancing arm muscle strength, which is a key factor in shot put performance.The research method used in this study is Classroom Action Research (CAR) following the Kemmis and McTaggart model. The study was conducted in several cycles, each consisting of planning, implementation, observation, and reflection. The research design included pre-test and post-test assessments to measure the effectiveness of push-up training on shot put performance. Data analysis was carried out using the Shapiro-Wilk normality test and the Paired Sample t-Test.The results showed that the pre-test and post-test data were normally distributed. The t-test indicated a significant improvement in shot put performance after push-up training. The average pre-test score of 61.56 increased to 72.50 in the post-test, with a mean difference of 10.94 points. These findings suggest that push-up training positively influences arm muscle strength and shot put performance.